Long-Term Treatment of Cuban Policosanol Attenuates Abnormal Oxidative Stress and Inflammatory Response via Amyloid Plaques Reduction in 5xFAD Mice - Jin-Ho Kim; Dong-Kyun Lim; Yoo-Hun Suh; Keun-A Chang (MDPI AG, 2021)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder resulting in cognitive decline or dementia, the number of patients with AD is continuously increasing. Although a lot of great progress has been made in research and development of AD therapeutics, there is no fundamental cure for this disease yet. This study demonstrated the memory-improving effects of Cuban policosanol (PCO) in 5xFAD mice, which is an animal model of AD. Following 4-months of treatment with PCO in 5xFAD mice, we found that the number of amyloid plaques decreased in the brain compared to the vehicle-treated 5xFAD mice. Long-term PCO treatment in 5xFAD mice resulted in the reduction of gliosis and abnormal inflammatory cytokines level (interleukin [IL]-1β, IL-6, and tumor necrosis factor [TNF]-α) in the cortex and hippocampus. Levels of lipid peroxide (4-hydroxynonenal [4-HNE]) and superoxide dismutase (SOD1 and SOD2) levels were also recoverd in the brains of PCO-treated 5xFAD mice. Notably, PCO administration reduced memory deficits in the passive avoidance test, as well as synaptic loss (PSD-95, synaptophysin) in 5xFAD mice. Collectively, we identified the potential effects of PCO as a useful supplement to delay or prevent AD progression by inhibiting the formation of Aβ plaques in the brain.